Constructing an Environmental, Social, And Governance (ESG) Index For Islamic Social Finance Institutions: Empirical Investigation From Indonesia - Ryandono, Muhammad Nafik Hadi; Widiastuti, Tika; Mawardi, Imron; Al Mustofa, Muhammad Ubaidillah; Robani, Anidah; Fanani, Sunan; Dewi, Eka Puspa; Atiya, Nikmatul; Rusanti, Ega; Nisa', Mir'atun (Journal of Ecohumanism, 2024)
This study constructs an index to measure the performance of Islamic Social Finance (ISF) Institutions based on Environmental, Social, and Governance (ESG) dimensions. This quantitative research employs the Delphi Analytical Network Process (DANP) and Multistage Weight Index (MWI). The index is constructed using DANP, conducting empirical assessments using MWI, then developing indicators using Focus group discussion (FGD), in-depth interviews, and structured surveys. This study also empirically tests index's implementation on five ISF institutions in Indonesia. The high score of the governance factor in this study indicates that the five ISF institutions are still focused on enhancing governance. This ESG index for ISF institutions create in this research may cannot be applied generally to other nations or institutions. But this ESG-building indicators still can be utilized as a reference for adopting ESG in other institutions. This study contributes to the literature by creating an ESG index for ISF institutions, where more research is needed. The notion of ESG is connected to maqashid sharia and is particularly essential in how institutions execute good governance and social issues while focusing on environmental protection.